Topologically Associating Domains and Regulatory Landscapes in Development, Evolution and Disease - Tena, Juan J.; Santos-Pereira, José M. (Frontiers in Cell and Developmental Biology, 2021)
Animal genomes are folded in topologically associating domains (TADs) that have been linked to the regulation of the genes they contain by constraining regulatory interactions between cis-regulatory elements and promoters. Therefore, TADs are proposed as structural scaffolds for the establishment of regulatory landscapes (RLs). In this review, we discuss recent advances in the connection between TADs and gene regulation, their relationship with gene RLs and their dynamics during development and differentiation. Moreover, we describe how restructuring TADs may lead to pathological conditions, which explains their high evolutionary conservation, but at the same time it provides a substrate for the emergence of evolutionary innovations that lay at the origin of vertebrates and other phylogenetic clades.